Taxonomic notes on the genus Gribodia Zavattari, 1912 (Hymenoptera: Vespidae: Eumeninae) from Vietnam and China, with description of a new species - Nguyen, Lien Thi Phuong; Xu, Zaifu (Zootaxa, 2015)
The genus Gribodia Zavattari, 1912, is newly recorded from Vietnam and China. Gribodia nigra sp. nov. (China, Hainan) is described and figured and G. cupreipennis (Bingham) is redescribed. A key to six known species of the genus is provided.